A survey of selected soil and litter invertebrate species from the northern Jarrah (Eucalyptus marginata) forest of Western Australia, with particular reference to soil-type, stratum, seasonality and the conservation of forest fauna - Majer, Jonathan; Postle, A. C.; Bell, D. T. (1991)
The soil and litter fauna was sampled at monthly intervals over 16 months from two lateritic sites and one Murray River loam site near DweUingup, Western Australia. Animals were obtained from the samples by heat extractor funnels and, following counts at the ordinal level, selected taxa were separated to species level for five periods which were representative of the major seasonal trends.A total of 290 species was separated. Of these, the most diverse were the Acarina (> 109 species), followed by the Collembola (60), Pauropoda (40), Hymenoptera (37), Thysanoptera (16), Diplopoda (12) and Psocoptera (11). Of the remaining taxa which were studied, lower numbers of species of Isoptera, Pseudoscorpionida and Symphyla were also obtained. Finally, the need to include invertebrates in research programmes which are directed towards the management and conservation of forest ecosystems is discussed. Some of the logistic and resource considerations which need to be taken into account when studying invertebrates are then reviewed.